2012
DOI: 10.3329/bjms.v11i3.11723
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic and acute anti-inflammatory effect of the ethanolic extract of the leaves of Paederia foetida (EEPF) on experimental animal models

Abstract: Objective:To study the analgesic and acute anti-inflammatory effect of the ethanolic extract of the leaves of Paederia foetida (EEPF) on experimental animal models. Materials and Methods: Fresh leaves were collected, air-dried, powdered, and percolated in 95% ethanol. Acute toxicity test was done according to OECD guidelines. Healthy albino rats (150-200 gm) of either sex were taken and divided into five groups with six animals in each group for central analgesic activity by tail flick method. Peripheral analg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…There also exist reports of methanolic and hexane extracts of this herb offering an anti-nociceptive effect measured by a reduction in writhing in rats administered with acetic acid (Wang et al, 2014). A study by Das et al (2012) showed that Paederia leaf extract in ethanol had an anti-nociceptive effect by demonstrating an increase in tail flicking time, and an anti-inflammatory effect based on rat paw oedema volume reduction. A 100 mg/kg body weight oral administration of desiccated methanolic extract of Paederia foetida leaves diminished paw oedema induced by injecting turpentine oil in Swiss albino rats by 45%.…”
Section: Paederia Foetida Lmentioning
confidence: 99%
“…There also exist reports of methanolic and hexane extracts of this herb offering an anti-nociceptive effect measured by a reduction in writhing in rats administered with acetic acid (Wang et al, 2014). A study by Das et al (2012) showed that Paederia leaf extract in ethanol had an anti-nociceptive effect by demonstrating an increase in tail flicking time, and an anti-inflammatory effect based on rat paw oedema volume reduction. A 100 mg/kg body weight oral administration of desiccated methanolic extract of Paederia foetida leaves diminished paw oedema induced by injecting turpentine oil in Swiss albino rats by 45%.…”
Section: Paederia Foetida Lmentioning
confidence: 99%
“…Mature fresh leaves of Vitex negundo have analgesic and anti-inflammatory properties [46], so the leaves can be used for neck pain or sprain. The same applies to Cissus quadrangularis, Paederia foetida and Datura metel [47][48][49]. Thus the three plants in combination can be useful against neck pain and nerve sprain.…”
Section: Commelina Benghalensis L Commelinaceae Boro Kendra Rootmentioning
confidence: 99%
“…(Rubiaceae family) has been used in Thai cuisine and Thai traditional medicine for diseases, including rheumatoid arthritis (Dixit, 2013;Kumar et al, 2015), diarrhea (Afroz et al, 2006), asthma (Macwan, 2010), and relieving diabetes (Kumar, 2014), in the southern region including Thailand. Phytochemical analysis revealed that P. foetida is rich in lupeol, ursolic acid, and beta-sitosterol (Dwivedi et al, 2018), which are shown to have their biological activities, including antiinflammatory (Das et al, 2012), antioxidant (Upadhyaya, 2013), antidiabetic (Morshed et al, 2012), andanticancer (Reddy et al, 2011) activities. Although the use of this plant is widespread, information about its toxicity-related issues is still limited (Reddy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%